Effect of the preparation method on the catalytic activity and stability of Au/Fe2O3 catalysts in the low-temperature water-gas shift reaction - M.A. Soria (2014)
The low temperature water-gas-shift reaction has been studied over a series of nanosized Au/Fe2O3 catalysts. The effect of the synthesis method on the catalytic activity has been analysed. A series of catalysts with different Au loadings has been prepared by different methods: deposition-precipitation (DP), liquid phase reductive deposition (LPRD) and double impregnation method (DIM). The Au/Fe2O3 catalysts prepared by DP showed the highest CO conversion. The catalysts were characterised by hydrogen temperature programmed reduction (TPR-H-2), high-resolution transmission electron microscopy (HRTEM), X-ray powder diffraction and X-ray photoelectron spectroscopy. TPR-H-2 analysis revealed that gold promotes the reducibility of the Fe2O3 support, which is crucial in this redox reaction. HRTEM evidences a very good dispersion of gold over the iron support, with nanoparticles in the range 2.2-3.1 nm for the DP and LPRD series, and a negligible increase in the average particle size of the used samples. For the DIM series, much larger Au particles (similar to 6.6 nm) were obtained.